Analysis of Level of Service at Jati Raya Street Semarang during New Normal Covid-19 Pandemic - Suharyo, Seno; Widyarini, Galih; Pratiwi, Yesina Intan (Science and Technology Research Centre, Universitas PGRI Semarang, 2021)
Jati Raya Street is one of the streets in Banyumanik district, Semarang, where many vehicles pass. Before the Covid-19 pandemic, the traffic jam usually occurs at certain hours because of people activities passing through this street. The purpose of this research is to know the degree of saturation and the street level of service from the volume / capacity ratio during New Normal condition on Covid-19 pandemic. The primary data survey is by measuring the street width and counting the two-way traffic volume. The survey was held on Monday, 9 November 2020, at 06.15 - 08.15, 11.05 - 13.05, and 16.05 - 17.05. From the survey results, the maximum traffic flow is 784 pcu/hour, the time is at 07.15 - 08.15, and the traffic direction is from Pasar Jati toward Sukun Raya street. The street capacity is 2371 pcu/hour, with a 0,33 degree of saturation. The street level of service based on this survey is B, which means, steady traffic flow, the driver has enough option to control the vehicle speed. This research was done during New Normal condition on Covid-19 pandemic, where there is a decrease on the number of vehicles that passing through this street, for some reasons, which one of them is because the school activities is using an online methods, so that students can study from home, without the needs of parents taking them to school and picking them up from school.Keywords: capacity, degree of saturation, level of service